Bakterielle Sepsis: Diagnostik und kalkulierte Antibiotikatherapie = Bacterial sepsis : diagnostics and calculated antibiotic therapy - Richter, Daniel; Heininger, Alexandra; Brenner, Thorsten; Hochreiter, Marcel; Dubler, Simon; Störzinger, Dominic; Pinder, Nadine; Hoppe-Tichy, Torsten; Weiterer, Sebastian; Zimmermann, Stefan; Weigand, Markus A.; Lichtenstern, Christoph (Der Anaesthesist, 2017)
The mortality of patients with sepsis and septic shock is still unacceptably high. An effective antibiotic treatment within 1 h of recognition of sepsis is an important target of sepsis treatment. Delays lead to an increase in mortality; therefore, structured treatment concepts form a rational foundation, taking relevant diagnostic and treatment steps into consideration. In addition to the assumed focus and individual risks of each patient, local resistance patterns and specific problem pathogens must be taken into account for selection of anti-infection treatment. Many pathophysiological alterations influence the pharmacokinetics of antibiotics during sepsis. The principle of standard dosing should be abandoned and replaced by an individual treatment approach with stronger weighting of the pharmacokinetics/pharmacodynamics (PK/PD) index of the substance groups. Although this is not yet the clinical standard, prolonged (or continuous) infusion of beta-lactam antibiotics and therapeutic drug monitoring (TDM) can help to achieve defined PK targets. Prolonged infusion is sufficient without TDM but for continuous infusion TDM is basically necessary. A further argument for individual PK/PD-oriented antibiotic approaches is the increasing number of infections due to multidrug resistant pathogens (MDR) in the intensive care unit. For effective treatment antibiotic stewardship teams (ABS team) are becoming more established. Interdisciplinary cooperation of the ABS team with infectiologists, microbiologists and clinical pharmacists leads not only to a rational administration of antibiotics but also has a positive influence on the outcome. The gold standards for pathogen detection are still culture-based detection and microbiological resistance testing for the various antibiotic groups. Despite the rapid investigation time, novel polymerase chain reaction (PCR)-based procedures for pathogen identification and resistance determination, are currently only an adjunct to routine sepsis diagnostics due to the limited number of studies, high costs and limited availability. In complicated septic courses with multiple anti-infective treatment or recurrent sepsis, PCR-based procedures can be used in addition to therapy monitoring and diagnostics. Novel antibiotics represent potent alternatives in the treatment of MDR infections. Due to the often defined spectrum of pathogens and the practically absent resistance, they are suitable for targeted treatment of severe MDR infections (therapy escalation).